Peningkatan Hasil Belajar Matematika dengan Model Pembelajaran Kooperatif Tipe Stad Bagi Siswa Kelas V SDN 25 Muaro Takung Kec. Kamang Baru - Syafni Maria Virgo (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
Mathematics is one of the subjects studied from basic education to tertiary institutions. Mathematics has an important role to equip students with the ability to think logically, analytically, systematically, critically and creatively, and the ability to work together. This research uses cooperative learning model type STAD which is a classroom action research. This research is based on the fact in the field that there are still many elementary school (SD) students who experience difficulties in adding the unequal denominated ordinary fractions. To overcome this, actions were taken using the STAD cooperative learning model. The purpose of this study was to improve the mathematics learning outcomes of grade V SD students with the STAD cooperative learning model. Data collection was carried out by means of tests, questionnaires, observations and observation sheets and other instruments that support research. Based on the results of the study, it was found that the STAD type of cooperative learning model can improve mathematics learning outcomes for learning the addition of ordinary fractions with the not the same name at SDN 25 Muaro Takung Kec, Kamang Baru. STAD type cooperative learning is carried out in 6 steps: